A novel approach for predicting the evolutionary origin of acquisition of foreign genes in bacteria: application of codon usage analyses - Khan, Md. Moazzem Hossain (BRAC University, 2012)
This thesis is submitted in a partial fulfillment of the requirement for the Degree of Masters in Biotechnology .